The impact of middle managers’ digital leadership on employee work engagement - Li, Zhenli; Yang, Cuibai; Yang, Zhuohang; Zhao, Yunlu (Frontiers in Psychology, 2024)
Background: In the rapidly evolving digital landscape, the role of middle managers in organizational structures and processes is increasingly pivotal. Positioned at the nexus of strategic directives and operational execution, they play an important role in driving digital transformation. This study discusses the underexamined domain of middle managers' digital leadership and its impact on employee work engagement in the context of digital transformation.Design: Drawing on Social Exchange Theory, this study investigates the influence of middle managers' digital leadership on employee work engagement through the analysis of survey data from 559 respondents across 11 listed companies in Southwest China. It examines the roles of employee empowerment and affective commitment as pivotal mediating variables and investigates the moderating effect of emotional intelligence in these relationships.The study aims to elucidate the mechanisms by which middle managers' digital leadership fosters employee work engagement, highlighting the importance of emotional intelligence, empowerment, and affective commitment in this process.The study reveals that middle managers' digital leadership has a significant positive impact on employee work engagement. Employee empowerment and affective commitment serve as mediating factors in the relationship between middle managers' digital leadership and employee work engagement. Emotional intelligence moderates the effect of middle managers' digital leadership on employee empowerment. Meanwhile, emotional intelligence further moderates the chain mediating of employee empowerment and affective commitment between middle managers' digital leadership and employees' work engagement.Implications: This research offers valuable insights into the dynamics of leadership and engagement in the digital era, emphasizing the need for organizations to foster digital leadership capabilities in middle management. It provides practical implications for enhancing employee work engagement